Agronomic performance and farmer preferences for biofortified orange-fleshed sweetpotato varieties in Zimbabwe - Jogo, W.; Nsingo-Kudita, Sakile; Munda, E.; Chiduwa, M.; Pinkson, S.; Gwaze, T. (International Potato Center, 2021)
This report summarizes the findings of a study carried out to evaluate the agronomic performance and sensory acceptance by small holder farmers of six biofortified orange-fleshed sweetpotato (OFSP) varieties that were first introduced from CIP’s sweetpotato breeding hub for Southern Africa in Mozambique. The study was participatory and carried out under different agroecological environments in Zimbabwe. The six OFSP varieties, namely Alisha, Victoria, Delvia, Sumaia, Namanga and Irene were planted in the 2019/20 agricultural season along with two non-biofortified white-fleshed local varieties, namely Chingova and German II, at seven DR&SS research stations (Kadoma, Marondera, Harare, Henderson, Gwebi, Makoholi and Panmure) and 120 farmer managed on-farm trial sites in 12 LFSP districts of Bindura, Gokwe North, Gokwe South, Guruve, Kwekwe, Makoni, Mazowe, Mount Darwin, Mutasa, Mutare, Shurugwi and Zvimba. At all but one of the research stations, two trials were set up, one under irrigation and the other under rain-fed conditions. On-farm trials were established following the Mother-Baby Trial approach with 2 mother trials and 8 baby trials per district. In each of the districts, one mother trial was planted under irrigation while the other was rain-fed. All the baby trials were rain-fed.